2021
DOI: 10.4103/aca.aca_17_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Intranasal Dexmedetomidine v/s Midazolam for Sedation of Pediatric Patients During Transthoracic Echocardiography

Abstract: Background: Procedural sedation required to improve the quality of Transthoracic Echocardiography (TTE) in infants and children. The ideal drug and route for sedation in children should have a rapid and reliable onset, atraumatic, palatable with minimal side effects, and rapid recovery. So, the aim of our study to evaluate and compare the efficacy and safety of intranasal midazolam and intranasal dexmedetomidine in pediatric patients for sedation during TTE. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…[17][18] Intranasal dexmedetomidine, intranasal ketamine, oral chloral hydrate, and intranasal midazolam have been described as perhaps more suitable options. 9,12,[14][15][16]18 Dexmedetomidine is a highly selective alpha-2 agonist that provides anxiolysis, mild analgesia, and cooperative sedation without respiratory depression. 19 It decreases central nervous system sympathetic outflow in a dose-dependent manner and can be administered intranasally for procedural sedation which is ideal when attempts to minimise traumatic administration via intravenous or intramuscular routes are taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[17][18] Intranasal dexmedetomidine, intranasal ketamine, oral chloral hydrate, and intranasal midazolam have been described as perhaps more suitable options. 9,12,[14][15][16]18 Dexmedetomidine is a highly selective alpha-2 agonist that provides anxiolysis, mild analgesia, and cooperative sedation without respiratory depression. 19 It decreases central nervous system sympathetic outflow in a dose-dependent manner and can be administered intranasally for procedural sedation which is ideal when attempts to minimise traumatic administration via intravenous or intramuscular routes are taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam, a benzodiazepine, is the most commonly studied procedural sedation drug and can be administered either intranasally or orally; however, it provides no analgesia and is associated with adverse events such as post-operative behavioural changes, cognitive impairment, paradoxical reactions, and respiratory depression. 9,16 Additionally, intranasal midazolam is known to provide nasal irritation and burning. 28 On the contrary, intranasal ketamine is used for its pain controlling aspect and may provide less bradycardia than dexmedetomidine but is not devoid of adverse events such as gastrointestinal tract stimulation, excessive salivation, nystagmus, an increased incidence of emergence agitation, and an unpleasant bitter taste.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 8 ] It has been widely used as a premedication in pediatric patients for procedural sedation and premedication, where it has shown promising results. [ 9 10 11 12 ] Hussain et al have reported in the literature that dexmedetomidine when administered through the nebulization route had reduced stress response to laryngoscopy and intubation. [ 13 ] Thomas D et al also reported that nebulized dexmedetomidine can attenuate the postoperative sore throat in patients.…”
Section: Introductionmentioning
confidence: 99%